Analysis of m6A methylation in skin tissues of different sex Liaoning cashmere goats. Issue 2 (3rd April 2023) - Wang, Yanru; Li, Gaoqian; Zhang, Xinjiang; Zheng, Yuanyuan; Guo, Suling; Guo, Dan; Zhang, Xinghui; Dou, Xingtang; Hui, Taiyu; Yue, Chang; Sun, Jiaming; Guo, Suping; et al.
Abstract: N 6 -methyladenosine (m 6 A) is the most frequent internal modification of mRNA and lncRNA in eukaryotes. We used two high-throughput sequencing method, m 6 A-seq and RNA-seq to identify pivotal m 6 A-modified genes in cashmere fineness and fiber growth. 8062 m 6 A peaks were detected by m 6 A-seq, including 2157 upregulated and 6445 downregulated. Furthermore, by comparing m 6 A-modified genes of the male Liaoning Cashmere Goat (M-LCG) and female Liaoning Cashmere Goat (F-LCG) skin tissues, we get 862 differentially expressed m 6 A-modified genes. To identify differently expressed m 6 A genes associated with cashmere fineness, 11 genes were selected for validation using real time fluorescent quantitative PCR in M-LCG and F-LCG. This study provides an acadamic basis on the molecular regulation mechanism of m 6 A modification in cashmere growth process.